Proceedings of the 15th Annual International Conference on Mobile Computing and Networking 2009
DOI: 10.1145/1614320.1614343
|View full text |Cite
|
Sign up to set email alerts
|

Optimal beam scheduling for multicasting in wireless networks

Abstract: We consider the problem of efficient link-layer multicasting in wireless networks with switched beamforming antennas. The inherent tradeoff between multicasting and beamforming -the broadcast advantage of low-gain omni-directional transmissions versus the high-gain but spatially restricted transmissions of beamforming antennas -makes this problem especially challenging. In this paper, we design and evaluate optimal algorithms, and easy-to-implement greedy algorithms with performance guarantees, that generate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 17 publications
0
52
0
Order By: Relevance
“…However, we neither discussed joint routing and cooperation across different flows, nor did we discuss MAC-layer scheduling under the MCB model. Specifically, due to beamforming, the nature of interference is different from the interference caused by omnidirectional wireless broadcasts, and hence the scheduling problem requires special treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, we neither discussed joint routing and cooperation across different flows, nor did we discuss MAC-layer scheduling under the MCB model. Specifically, due to beamforming, the nature of interference is different from the interference caused by omnidirectional wireless broadcasts, and hence the scheduling problem requires special treatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…In [2], an online routing through multicast communication is proposed in order to maximize the lifetime of a network. In [3], a multicast model is defined using a composite beam pattern, which is defined depending on whether the beam's transmission power is equally split or asymmetrically split.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by concentrating the transmission energy in a specific direction, beamforming creates a signal that is orders of magnitude stronger than that of the signals in other directions. One can further reduce interference in a network by combining beamforing feature with power control [5] and scheduling [1], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover it considers only a restricted form of sensors in which a sensors covers only a single directional beam. It has been shown that such a restriction for antennas results in a sub-optimal network performance [6]. In this paper, we consider a general antenna model and find the optimal wireless plan that satisfies a prespecified performance constraint for all the network users.…”
Section: Introductionmentioning
confidence: 99%